The Effect of An Institution’s Environment, Leadership, Inspiration for Accomplishment, and Work Happiness on the Performance of Teachers in Medan Aliyah Negeri (MAN) - Siti Aisyah Hanim; Zainuddin Zainuddin; Darwin Darwin (Randwick International of Education and Linguistics Science Journal, 2022)
This research was conducted to identify: (1) the impact of an institution’s environment on inspiration for accomplishment, (2) the impact of transformational Leadership on motivation to succeed, (3) the influence of an institution’s environment on work happiness, (4the effect of transformational Leadership on work happiness, (5) the role of an institution’s environment on work happiness, organisation behavior on teachers’ works, and (6) the impact of transformational Leadership on teachers’ works (7) the impact of inspiration for accomplishment on teachers’ works, and (8) the impact of work satisfaction on teachers’ works. The subject of the study was the Madrash Aliyah Negeri teacher of Medan City with a total sample of 182 participants obtained by filtered proportionally random sampling. The data collected were analyzed using path analysis after measuring the correlation of all research variables in the form of a matrix. The investigation of the influence of exogenous factors on endogenous variables derived in each substructure (1) inspiration for accomplishment is influenced by an institution’s environment and transformational Leadership by 0.229 and 0.176, respectively, (2) work happiness is influenced by an institution’s environment and transformational Leadership by 0.077 and 0.047, respectively, (3) teachers’ works is influenced by organisation behavior, transformational Leadership, inspiration for accomplishment, and work.